Flame Atomic Emission and Colorimetric Methods for the Determination of Cephalexin Monohydrate in Pharmaceutical Preparations (Baghdad Science Journal, 2016)
We propose two simple, rapid, and convenient spectrophotometric methods which are described for the determination of cephalexin in bulk and its pharmaceutical preparations. They are based on the measurement of the flame atomic emission of potassium ion (in the first method) and colorimetric determination of the green colored solution at 610 nm formed after the reaction of cephalexin with potassium permanganate as an oxidant agent (in the second method) in basic medium. The working conditions of the methods are investigated and optimized. Beer's law plot shows a good correlation in the concentration range of 5-40?g ml-1. The detection limits are 2.573,2.814 ?g ml-1 for the flame emission photometric method and 1.844,2.016 ?g ml-1 for colorimetric methods for capsules and suspensions respectively.The methods are successfully applied to the determination of cephalexin in capsules and suspensions, and the obtained results are in good agreement with the label claim. No interference is observed from the commonly encountered additives and excipients.